THE ROLE OF SPIRITUAL AND MORAL VALUES IN DEVELOPING A CULTURE OF RELATIONSHIPS WITH YOUTH IN THE FAMILY (The Conference Hub, 2025)
This article explores the critical role of spiritual and moral values in fostering healthy relationships within families, particularly among youth. It emphasizes how these values serve as foundational elements that guide behavior, shape character, and influence interpersonal dynamics. By examining various cultural perspectives and psychological theories, the article highlights the importance of nurturing an environment where spiritual and moral teachings are integrated into daily family interactions. The research underscores the need for families to actively engage in discussions about values, ethics, and spirituality to promote emotional well-being and resilience in young individuals. Ultimately, the article advocates for a holistic approach to family relationships that prioritizes spiritual and moral development as a means to cultivate strong, supportive bonds among family members.